ANALISIS REPRESENTASI TEORI HELIOSENTRIS DALAM ANIME ‘ORB:ON THE MOVEMENTS OF THE EARTH’ DAN DAMPAKNYA TERHADAP KONSEP ILMU FALAK - Sulkifli, Muh.; Laman, Ilham (HISABUNA: Jurnal Ilmu Falak, 2026)
ABSTRACT This study is based on the problem of low astronomical literacy in Muslim society, especially in understanding the movement of celestial bodies that affect worship practices such as determining the direction of the Qibla and prayer times. This article aims to answer how the representation of the heliocentric theory in the anime Orb: On the Movements of the Earth and what its implications are for concepts in astronomy. This study is a qualitative study with primary data sources in the form of the anime Orb: On the Movements of the Earth and secondary sources in the form of literature related to astronomy and Islamic astronomy. Data collection techniques are carried out through library studies and visual observations of anime content, then analyzed using content analysis methods with an interdisciplinary approach between modern astronomy and Islamic astronomy. The results of the study show that this anime represents the heliocentric theory visually and narratively through astronomical symbols and historical narratives. The implementation of this concept in anime effectively simplifies complex scientific theories. From the perspective of astronomy, the heliocentric theory is understood as a manifestation of the order of God's creation that supports the accuracy of determining the direction of the Qibla, prayer times, and the Hijri calendar. This finding confirms the harmony between modern science and Islamic values. The implications of this study confirm that modern visual media can be a link between contemporary science and Islamic scientific traditions, as well as opening up opportunities for interdisciplinary learning approaches in Islamic educational institutions.